What are the important morbidities associated with paediatric cardiac surgery? A mixed methods study - Stephen Morris; Serban Stoica; Andrew Parry; Christina Pagel; Jo Wray; David J Barron; Karen Sheehan; Kathleen Selway; Lyvonne Tume; Jane Cassidy; Alison Jones; John Stickley; et al. (BMJ Open)
Objectives Given the current excellent early mortality rates for paediatric cardiac surgery, stakeholders believe that this important safety outcome should be supplemented by a wider range of measures. Our objectives were to prospectively measure the incidence of morbidities following paediatric cardiac surgery and to evaluate their clinical and health-economic impact over 6 months.Design The design was a prospective, multicentre, multidisciplinary mixed methods study.Setting The setting was 5 of the 10 paediatric cardiac surgery centres in the UK with 21 months recruitment.Participants Included were 3090 paediatric cardiac surgeries, of which 666 patients were recruited to an impact substudy.Results Families and clinicians prioritised:Acute neurological event, unplanned re-intervention, feeding problems, renal replacement therapy, major adverse events, extracorporeal life support, necrotising enterocolitis, postsurgical infection and prolonged pleural effusion or chylothorax.Among 3090 consecutive surgeries, there were 675 (21.8%) with at least one of these morbidities. Independent risk factors for morbidity included neonatal age, complex heart disease and prolonged cardiopulmonary bypass (p<0.001). Among patients with morbidity, 6-month survival was 88.2% (95% CI 85.4 to 90.6) compared with 99.3% (95% CI 98.9 to 99.6) with none of the morbidities (p<0.001). The impact substudy in 340 children with morbidity and 326 control children with no morbidity indicated that morbidity-related impairment in quality of life improved between 6 weeks and 6 months. When compared with children with no morbidities, those with morbidity experienced a median of 13 (95% CI 10.2 to 15.8, p<0.001) fewer days at home by 6 months, and an adjusted incremental cost of £21 292 (95% CI £17 694 to £32 423, p<0.001).Conclusions Evaluation of postoperative morbidity is more complicated than measuring early mortality. However, tracking morbidity after paediatric cardiac surgery over 6 months offers stakeholders important data that are of value to parents and will be useful in driving future quality improvement.